2018
DOI: 10.1155/2018/2748274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Novel Formulation on Oral Biofilm, pH Buffering, and Gingival Health in Patients with Dry Mouth

Abstract: Goal To identify in patients with dry mouth the effects of a novel test agent (Oral Essentials Hydrating Formula Mouthwash, Beverly Hills, CA) versus a control agent (Biotène Dry Mouth Oral Rinse, GlaxoSmithKline Consumer Healthcare L.P., Moon Township, PA, USA) versus no treatment on dry mouth, plaque, salivary pH and buffering capacity, gingival health, and tooth sensitivity. Materials and Methods In this cross-over study, ten subjects with dry mouth used test and control dry mouth interventions, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The improved buffering capacity was also observed in elderly patients after using OMJ [ 25 ]. In addition, a crossover study in participants with hyposalivation showed similar findings after using Biotene Dry Mouth Oral Rinse and a novel mouthwash product [ 36 ]. Because saliva buffering capacity plays an important role in maintaining a neutral oral environment, it would be of value to investigate the long-term effects of OMJ on oral and dental conditions in these patients.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The improved buffering capacity was also observed in elderly patients after using OMJ [ 25 ]. In addition, a crossover study in participants with hyposalivation showed similar findings after using Biotene Dry Mouth Oral Rinse and a novel mouthwash product [ 36 ]. Because saliva buffering capacity plays an important role in maintaining a neutral oral environment, it would be of value to investigate the long-term effects of OMJ on oral and dental conditions in these patients.…”
Section: Discussionmentioning
confidence: 87%
“…This was in concordance with previous studies that evaluated the effects of Bioxtra gel in head and neck cancers and OMJ in elderly participants [ 25 , 35 ]. In addition, Biotene Dry Mouth Oral Rinse and a novel mouthwash product were shown to improve saliva pH in xerostomic participants [ 36 ]. Both OMJ and GC products have neutral pH, which may be important for the improved saliva pH observed in the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Mouth rinses, mouthwashes, and toothpaste can provide short-term relief from dry mouth and keep the patient’s mouth, teeth, and gums healthy. Such mouth rinses can greatly increase saliva volume and improve pH buffering [ 131 ]. However, similar to saliva substitutes, these treatments only treat symptoms for a short period of time (up to 4 h) and do not solve the underlying clinical problem.…”
Section: Increasing Prevalence Of Xerostomiamentioning
confidence: 99%
“…Oral Rinses, Mouthwashes, and Toothpastes Oral rinses, mouthwashes, and toothpastes can provide short-term relief from oral dryness and maintain the health of the mouth, teeth, and gums. Such oral rinses are able to significantly increase the volume of saliva production and improve pH buffering [48]. However, like the saliva substitutes described above, these therapeutics merely treat the symptoms for a short period (up to 4 hours) and do not address the underlying clinical problem.…”
Section: Saliva Substitutesmentioning
confidence: 99%